THE EFFECT OF BILE ACID SIGNALING PATHWAY ON LUNG IMMUNE CELLS IN LIVER FIBROTIC MICE MODEL - Alfuqaha, Ala`a (An-Najah National University, 2024)
Background: Patients with liver diseases are at high risk for the development of acute respiratory distress syndrome (ARDS). The mechanisms by which the liver participates in the pathogenesis of acute lung injury are not understood. Objectives: Our study aims to assess for mediators that could interfere with liver-lung axis via studying the involvement of bile acids (BAs) signaling in the lung in a mouse model of liver fibrosis. Methods: C57BL/6J mice were induced for liver fibrosis through i.p injection with carbon-tetrachloride (CCl4) for 2 weeks (as an acute model) and 6 weeks (as a chronic model) (n = 12). Serum, BALF, and lung tissue samples were collected on sacrificing day. ELISA was used to detect levels of sRAGE and inflammatory cytokines (IL-1β, IL-4, IL-6, TNF-α) in BALF samples, and BAs in both serum and BALF. Real-time PCR was used to quantify markers of lung oxidation (GPx, GSH: GSSG, MDA, SOD), injury (SP-D1), and fibrosis (α-SMA, MMP-9, GFAP). Flow cytometry evaluated isolated resident lung NKs for activation and viability, through the expression of CD107a marker and NTCP. Isolate alveolar epithelial cells (AEC) type I and II were assessed for apoptosis. Results: BAs concentrations were linearly correlated with liver fibrosis severities in serum and BALF. It was found that markers of inflammation, oxidative stress, injury, and fibrosis were significantly increased in both the acute and chronic models of liver fibrosis compared to the control group. Isolated resident lung NK cells exhibited a significant increase in the expression of BA-specific transporter, NTCP, which was associated with a reduction in the expression of CD107a maker; the key indicator of NKs activation and functionality. Moreover, AECs type I and II demonstrated a substantial increase in their apoptosis rate, which was correlated with liver fibrosis severity. Conclusion: BAs, by-products of cholesterol generated in the liver, were found in high concentrations in the lungs of mice with liver fibrosis. These data were associated with an elevation in oxidative stress markers in the lung, and impairment of resident lung NK cells with overexpression of NTCP on their surface. BAs insults on NK cells may partly contribute to the acute lung injury (ALI) pathogenesis and AECs apoptosis. Our data suggest BAs as a valuable approach in treating and diagnosing of liver fibrosis and pulmonary complications. Keywords: Liver fibrosis, resident lung NK cells, BAs, BALF.
تأثير مسار إشارات حمض الصفراء على الخلايا المناعية للرئة في نموذج الفئران للتليف الكبدي